Evaluation of hospital inpatient complications: a planning approach - Lagoe, Ronald J (BioMed Central, 2010)
BACKGROUND: Hospital inpatient complications are one of a number of adverse health care outcomes. Reducing complications has been identified as an approach to improving care and saving resources as part of the health care reform efforts in the United States. An objective of this study was to describe the Potentially Preventable Complications software developed as a tool for evaluating hospital inpatient outcomes. Additional objectives included demonstration of the use of this software to evaluate the connection between health care outcomes and expenses in United States administrative data at the state and local levels and the use of the software to plan and implement interventions to reduce hospital complications in one U.S. metropolitan area. METHODS: The study described the Potentially Preventable Complications software as a tool for evaluating these inpatient hospital outcomes. Through administrative hospital charge data from California and Maryland and through cost data from three hospitals in Syracuse, New York, expenses for patients with and without complications were compared. These comparisons were based on patients in the same All Patients Refined Diagnosis Related Groups and severity of illness categories. This analysis included tests of statistical significance. In addition, the study included a planning process for use of the Potentially Preventable Complications software in three Syracuse hospitals to plan and implement reductions in hospital inpatient complications. The use of the PPC software in cost comparisons and reduction of complications included tests of statistical significance. RESULTS: The study demonstrated that Potentially Preventable Complications were associated with significantly increased cost in administrative data from the United States in California and Maryland and in actual cost data from the hospitals of Syracuse, New York. The implementation of interventions in the Syracuse hospitals was associated with the reduction of complications for urinary tract infection, decubitus ulcer, and pulmonary embolism. CONCLUSIONS: The study demonstrated that the Potentially Preventable Complications software could be used to evaluate hospital outcomes and related costs at the aggregate and diagnosis specific levels. It also indicated that the system could be used to plan and implement interventions to improve outcomes on an individual or multihospital basis.